Spontaneous hemothorax: A rare presentation of costal exostosis Spontan Hemotoraks: Nadir Bir Kostal Ekzostoz Sunumu - Muhamad Hud Muhamad Zin; Haron, H.; Ishamuddin, M.; Rahman, M.R.A.; Abdullah, M.F. (Gazi Universitesi, 2020)
Costal exostosis is a typically benign tumor growth of the rib that usually remains asymptomatic but sometimes can develop a severe complication such as hemothorax and required emergency surgery. At this moment, we presented a case of 20 years old gentleman with no previous history of trauma presented to our hospital with progressively worsening shortness of breath and computed tomography of chest show features of hemothorax. He subsequently underwent video-assisted thoracoscopic that found costal exostosis perforating the lung. The costal exostosis subsequently resected, and post-operatively he was discharged well. We, with this, presented a rare case of costal exostosis, along with the discussion on clinical presentation and management.